1997
DOI: 10.1128/mcb.17.11.6402
|View full text |Cite
|
Sign up to set email alerts
|

The 36-Kilodalton Embryonic-Type Cytoplasmic Polyadenylation Element-Binding Protein in Xenopus laevis Is ElrA, a Member of the ELAV Family of RNA-Binding Proteins

Abstract: The translational activation of several maternal mRNAs in Xenopus laevis is dependent on cytoplasmic poly(A) elongation. Messages harboring the UUUUUAU-type cytoplasmic polyadenylation element (CPE) in their 3 untranslated regions (UTRs) undergo polyadenylation and translation during oocyte maturation. This CPE is bound by the protein CPEB, which is essential for polyadenylation. mRNAs that have the poly(U) 12-27 embryonic-type CPE (eCPE) in their 3 UTRs undergo polyadenylation and translation during the early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 35 publications
3
53
1
Order By: Relevance
“…1C). Previous experiments revealed that both xCIRP2 and ElrA proteins are present predominantly in the oocyte cytoplasm (25,26). Xenopus oocyte lysates were prepared and subjected to immunoprecipitation with anti-xCIRP2 antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1C). Previous experiments revealed that both xCIRP2 and ElrA proteins are present predominantly in the oocyte cytoplasm (25,26). Xenopus oocyte lysates were prepared and subjected to immunoprecipitation with anti-xCIRP2 antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, upon UV irradiation, cytoplasmic fractions of both proteins are increased and are involved in stabilization of specific mRNAs (24,32). Third, both ElrA and xCIRP2 proteins are predominantly cytoplasmic in Xenopus oocytes (25,26). As a large stockpile of maternal mRNA is accumulated in the oocyte cytoplasm, ElrA and xCIRP2 may play roles in the control of poly(A) lengths of these mRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in Xenopus U-rich or C-rich CPEs initiate polyadenylation upon fertilization (Simon et al, 1992;Paillard et al, 2000). The mechanism by which the protein complexes that bind to CPEs accomplish polyadenylation is not known for activation (Paillard et al, 2000;Wu et al, 1997), but is better understood during oocyte maturation. During maturation, CPEs ultimately bind cytoplasmic polyadenylation specificity factor (CPSF), which recruits poly(A) polymerase to the 3ЈUTR (Mendez et al, 2000).…”
Section: Maternal Transcript Translationmentioning
confidence: 99%
“…With the exception of histone mRNA, most vertebrate mRNAs possess 39 poly(A) tails ranging from 100 to 200ϩ residues in length+ Poly(A) addition is one of the last steps in pre-mRNA processing, occurring prior to splicing of the terminal intron and nuclear export (Bauren & Wieslander, 1994)+ Based on the exon definition model, the 39 processing complex substitutes for a 59 splice site to define the end of the terminal exon (Berget, 1995), and there is good evidence linking 39 processing to splicing of the terminal intron (Lou et al+, 1996;Cooke et al+, 1999;Custodio et al+, 1999)+ This interaction between splicing and 39 processing plays a key role in regulating gene expression, particularly in cases involving exon selection linked to selection of alternative 39 ends (Lou et al+, 1999)+ Pre-mRNA 39 processing is regulated by cis-acting elements in the message body (reviewed in Zhao et al+, 1999)+ Upstream elements, or USEs, in HIV-1 proviral RNA (Gilmartin et al+, 1995), adenovirus late RNA (Sittler et al+, 1995), SV40 late RNA (Schek et al+, 1992), and C2 complement gene (Moreira et al+, 1998) can act as enhancers to stimulate 39 processing of their respective RNAs+ Conversely, U1A binding to a pair of U1A binding sites adjacent to AAUAAA in U1A pre-mRNA blocks poly(A) addition by inhibiting poly(A) polymerase without affecting the initial cleavage step (Gunderson et al+, 1994)+ Elements upstream of AAUAAA can also regulate poly(A) tail length+ Poly(A) length regulation has been best characterized for mRNAs that undergo deadenylation or poly(A) addition during various stages of egg maturation and embryonic development (reviewed in Richter, 1999)+ This form of regulation is cytoplasmic, and involves the interaction of the cytoplasmic polyadenylation element binding protein (CPE-BP) with a U-rich cytoplasmic polyadenylation element (CPE) upstream of AAUAAA (Wu et al+, 1997)+ Embryospecific deadenylation is controlled by a distinct upstream element, EDEN, through its interaction with EDEN-BP (Paillard et al+, 1998)+ The deadenylation ef-ficiency of the EDEN element is enhanced by the presence of upstream AUU repeats, suggesting an interplay between multiple cis-acting elements in regulating deadenylation (Audic et al+, 1998)+ In the course of studying the estrogen regulation of mRNA stability in Xenopus, we found that albumin and several other serum protein mRNAs have an unusually short, 17-nt poly(A) tail (Schoenberg et al+, 1989;Pastori et al+, 1991)+ Using an intron-specific primer in an RT-PCR assay for poly(A) tail length (Salles et al+, 1999), we subsequently identifi...…”
Section: Introductionmentioning
confidence: 99%